Pengaruh Modal Kerja Bersih, Solvabilitas, Dan Ukuran Perusahaan Terhadap Profitabilitas (Jurnal Kendali Akuntansi, 2023)
The purpose of this research is to analyze the effect of net working capital, solvency and company size on profitability. There are independent variables including net working capital using Net Working Capital, solvency using Debt to Equity Ratio, company size using natural logarithm of total assets and the dependent variable profitability using Net Profit Margin. The sample in this research uses the food and beverage sub-sector which is listed on the Indonesia Stock Exchange for the 2019-2021 period, publishes annual financial reports for 2019-2021, as well as entities with complete financial report data related to research variables, entities earn profits throughout 2019- 2021, entities that publish their financial reports in rupiah currency in 2019-2021 using the non-purposive sampling method. In this research, there were 20 entities that supported the research sample criteria, so that 60 financial report data were obtained. This research method uses classical assumption tests such as normality, multicollinearity, heteroscedasticity and autocorrelation used in this research. Furthermore, the hypothesis is tested with the F test, t test and the coefficient of determination. The research test uses multiple regression analysis with multiple regression equation models. Based on the test findings, it is known that working capital has no impact on profitability, solvency has a negative impact on profitability and company size has a positive impact on profitability in food and beverage sub-sector entities listed on the Indonesia Stock Exchange in 2019-2021.